Hotel Transylvania 3 “A Monster Vacation” Movie: Exploring Dialogue and Emotional Literacy - Arnoi, Khoirun Nisaa; Rahmah, Ilma Yullinda; Ridhawati, Listya Arum; Safi'i, Muhamad (Universitas Muhammadiyah Mataram, 2025)
This qualitative study employed content analysis to classify and critically interpret the illocutionary acts in the animated film Hotel Transylvania 3: